Long-term efficacy of catheter ablation as first-line therapy for paroxysmal atrial fibrillation: 5-year outcome in a randomised clinical trial. Issue 5 (26th August 2016) - Nielsen, Jens Cosedis; Johannessen, Arne; Raatikainen, Pekka; Hindricks, Gerhard; Walfridsson, Håkan; Pehrson, Steen Michael; Englund, Anders; Hartikainen, Juha; Mortensen, Leif Spange; Hansen, Peter Steen
Abstract : Objective: The Medical ANtiarrhythmic Treatment or Radiofrequency Ablation in Paroxysmal Atrial Fibrillation (MANTRA-PAF) trial compared radiofrequency catheter ablation (RFA) with antiarrhythmic drug therapy (AAD) as first-line treatment for paroxysmal atrial fibrillation (AF). Endpoint of ablation was elimination of electrical activity inside pulmonary veins. We present the results of the 5-year follow-up. Methods: This pre-specified 5-year follow-up included assessment of any AF and symptomatic AF burden by one 7-day Holter recording and quality of life (QoL) assessment, using SF-36 questionnaire physical and mental component scores. Analysis was intention-to-treat. Imputation was used to compensate for missing Holter data. Results: 245 of 294 patients (83%) randomised to RFA (n=125) or AAD (n=120) attended the 5-year follow-up, 227 with Holter recording. Use of class I or III AAD was more frequent in AAD group (N=61 vs 13, p<0.001). More patients in the RFA group were free from AF (126/146 (86%) vs 105/148 (71%), p=0.001, relative risk (RR) 0.82; 95% CI 0.73 to 0.93) and symptomatic AF (137/146 (94%) vs 126/148 (85%), p=0.015, χ 2 test, RR 0.91; 95% CI 0.84 to 0.98) in 7-day Holter recording. AF burden was significantly lower in the RFA group (any AF: p=0.003; symptomatic AF: p=0.02). QoL scores did not differ between randomisation groups. QoL scores remained improved from baseline (both components p<0.001), and did not differ from 2-year scores. Conclusions: At 5 years, the occurrence and burden of any AF and symptomatic AF were significantly lower in the RFA group than in the AAD group. Improved QoL scores observed after 2 years persisted after 5 years without between-group differences. Trial registration number: NCT00133211; Results.